HUBUNGAN ANTARA MOTIVASI BELAJAR DAN LATAR BELAKANG PENDIDIKAN DENGAN PRESTASI BELAJAR MAHASISWA DI AKADEMI KEPERAWATAN PATRIA HUSADA SURAKARTA - Yuliawan, Anton (Jurnal AKPER GSH, 2012)
The objective of the research :  For there any correlation between the learning motivation and the background of the education with the learning acheivement of academic student at the Patria Husada of Nursing Academy of Surakarta.The method of the research : The usage of research metode is survey method.  The Research Design is Correlative Descriptive. The technic sampling using total sampling. The Technic of Collecting Data extends : Observation, Dialoque, Quistionaire. The technic analisys of the data, using the logistic regression.The result of the research : Shows that variable learning motivation and the background of education has significant influence to the Acheivement of academic student  with each independent variable learning motivation has significant 0.028 and the background of education has significant 0.039 (p value < 0.05). From the equetation of the regression of the logistic found that  every unit of the increasing motivation will increase log of odds achievement 2.401 with expected 11,032. and every unit increasing of the education background will increase log of odds achievement 1.937 with expected 6.935.The Conclusion of Researche : There is the correlation between the learning motivation and the background of the education with the acheivement of academic student the Patria Husada of Nursing Academy of Surakarta. The mean is the high learning motivation with the background of education gived more the learning achievement of academic student in the Nursing Academic of Paria Husada Surakarta.  The Key words : Learning Motivation, The Background of  The Education, Learning Acheivement.